2019
DOI: 10.2337/db18-0557
|View full text |Cite
|
Sign up to set email alerts
|

Absence of TXNIP in Humans Leads to Lactic Acidosis and Low Serum Methionine Linked to Deficient Respiration on Pyruvate

Abstract: Thioredoxin-interacting protein (TXNIP) is an α-arrestin that can bind to and inhibit the antioxidant protein thioredoxin (TXN). TXNIP expression is induced by glucose and promotes β-cell apoptosis in the pancreas, and deletion of its gene in mouse models protects against diabetes. TXNIP is currently studied as a potential new target for antidiabetic drug therapy. In this study, we describe a family with a mutation in the TXNIP gene leading to nondetectable expression of TXNIP protein. Symptoms of affected fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…TXNIP is an important member of the body’s antioxidant stress response thioredoxin, mainly playing an oxidative stress role [24]. Recent studies have found that TXNIP can bind to and activate NLRP3 in a diseased state, thereby activating NLRP3 signaling pathway [22,24]. Our present data showed that Gal-3 regulates TXNIP/NLRP3 signaling pathway to promote neuroinflammation in SCI.…”
Section: Discussionsupporting
confidence: 57%
“…TXNIP is an important member of the body’s antioxidant stress response thioredoxin, mainly playing an oxidative stress role [24]. Recent studies have found that TXNIP can bind to and activate NLRP3 in a diseased state, thereby activating NLRP3 signaling pathway [22,24]. Our present data showed that Gal-3 regulates TXNIP/NLRP3 signaling pathway to promote neuroinflammation in SCI.…”
Section: Discussionsupporting
confidence: 57%
“…TXNIP knockout mice ( TXNIP KO) show impaired metabolic homeostasis, including adipogenesis and reduced gluconeogenesis [ 76 ], and decreased glucose uptake [ 77 ]. Similarly, a recently described human mutation demonstrated that diminished TXNIP function is linked to inefficient utilization of glucose [ 78 ]. Accordingly, glucose stress (hyperglycemia) upregulated TXNIP levels in 3T3LY adipocytes and was downregulated by IGF-1 and insulin ( Figure 5 A) [ 79 ].…”
Section: Gh/igf-1 Effects On Oxidative Stress During Agingmentioning
confidence: 99%
“…The α-arrestins are known as multifunctional scaffolding proteins involved in protein-protein interactions that mediate a wide array of signaling processes. 15 TXNIP is expressed in metabolically important sites like adipose tissue, liver, and skeletal muscles. It is also the main regulator of glucose balance in our system.…”
Section: Thioredoxin Interacting Proteinmentioning
confidence: 99%